2016
DOI: 10.1177/1687814016649116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of punch radius on elastic modulus of three-point bending tests

Abstract: Three-point bending is one of the most common methods of studying the mechanical performance of materials. The influence of punch radius in the measurements is not considered in the previous studies. This article focuses on the influence of the punch radius on the elastic modulus. The experiment is set up to measure the elastic modulus of 6061 aluminum alloy (6061 Al) and copper as the specimens, in which several different radii of punches are used. The maximum bending deflection of the middle point is 1.0 mm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The radius of the impactor was selected to achieve a radius-to-CLT-lamella-thickness ratio of 4 (i.e., 5.375 in/1.375 in). The radius of the impactor conforms to the recommendations of ASTM D198, radius of curvature 2-to-4 times the depth, and Hou [30], radius of curvature 2.5-to-3 times the depth. The impactor mass is 111.52 lbs (50.46 kg).…”
Section: Impulsive Center-point Testing System Designmentioning
confidence: 58%
“…The radius of the impactor was selected to achieve a radius-to-CLT-lamella-thickness ratio of 4 (i.e., 5.375 in/1.375 in). The radius of the impactor conforms to the recommendations of ASTM D198, radius of curvature 2-to-4 times the depth, and Hou [30], radius of curvature 2.5-to-3 times the depth. The impactor mass is 111.52 lbs (50.46 kg).…”
Section: Impulsive Center-point Testing System Designmentioning
confidence: 58%
“…During the simulation, the specimen was bent and the vertical reaction force was recorded (see Figure 8). The Poisson coefficient υ = 0.25 and the friction coefficient f = 0.15 were used in the same way as in [40] where the Kevlar/PVB specimens were also subjected to the three-point bending test. Due to the relatively large deformations (related to the size of the tested specimen), the simulation is defined as 'nonlinear' which allows us to consider the second-order effects.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Experimental tests were used as a baseline, and to validate the correctness of FEA. It was found that, with an increase in punch radius, the elastic modulus, peak load, and contact length also increased [18]. Note that only the crosshead motion was taken into account for the stress-strain calculations.…”
Section: Experimental Stress and Strain Behaviourmentioning
confidence: 99%